HLA antigens and acetylcholine receptor antibodies in penicillamine induced myasthenia gravis. - Garlepp, M J (1983)
Antibodies to the acetylcholine receptor and HLA antigens have been studied in patients with myasthenia gravis occurring in association with penicillamine treatment. The properties of the antiacetylcholine receptor in these patients differed from those in patients with idiopathic myasthenia gravis in terms of specificity and affinity. These patients had an increased prevalence of HLA Bw35 and DR1 compared to controls and a decreased frequency of B8 and DR3 compared to patients with idiopathic myasthenia gravis. Likewise, they had a decreased frequency of DR4 compared to patients with rheumatoid arthritis. These data provide supportive evidence for a role for penicillamine in the induction of myasthenia gravis in genetically predisposed individuals.